"Old" chemistry in a new context: photocleavable 2-oxoacetate-containing latex dispersions and core–shell microcapsules for the controlled release of volatile compounds1. Issue 17 (7th May 2015) - Charlon, Marine; Trachsel, Alain; Paret, Nicolas; Frascotti, Laurence; Berthier, Damien L.; Herrmann, Andreas
<x xml:space="preserve">Abstract</x> 2-Oxoacetates polymerised into nanoparticles or encapsulated in microcapsules are stable against hydrolysis and release fragrances on UVA irradiation.